The Evolution of Artificial Intelligence in Business Innovation: A Comprehensive Bibliometric Study - Fattah, Nanang; Budiman, Arief; Hanifah, Nisrina WIdi (Training & Research Institute - Jeramba Ilmu Sukses, 2024)
This study analyzes the relationship between Artificial Intelligence (AI) and business innovation using bibliometric methods. The results reveal that research trends in this field continue to grow, with a primary focus on AI applications in operational efficiency, business strategy, and product development. The study also identifies gaps in exploring the specific impact of AI on certain types of innovation and the lack of cross-disciplinary collaboration. These findings emphasize the relevance of this topic for future research, particularly in supporting technology-based business development.